Emotions in Language Learning: Understanding Foreign Language Enjoyment and Anxiety in Higher Education - Łodej, Monika; Osmoła, Agnieszka (Neofilolog, 2024)
The significant role of emotions in learning was reemphasized during school and university closures caused by the COVID-19 pandemic. However, upon returning to campus, cognitive learning outcomes have reclaimed a dominating position in the university curriculum, while affective learning appears to have been disregarded. The present study contributes to the discussion on the significance of social-emotional learning in higher education. Therefore, the primary objective of this inquiry is to trace the perceived levels of foreign language enjoyment (FLE) and foreign language classroom anxiety (FLCA) in order to understand factors which contribute to their emergence. The research sample comprises 108 Polish university students majoring in English and enrolled in a bachelor’s programme. The findings demonstrate that language enjoyment is more prevalent among participants than language anxiety. The causes of language enjoyment are associated with teacher-student and peer-peer interactions as well as the classroom atmosphere, while language anxiety is reported to be linked to the fear of negative evaluation of students’ academic performance, test anxiety, and communication apprehension. These results suggest that English Department students are not exempt from experiencing language classroom anxiety, and engaging in practical English classes may be a source of a range of positive and negative emotions.